1999
DOI: 10.1109/55.806099
|View full text |Cite
|
Sign up to set email alerts
|

Observation of oxide breakdown and its effects on the characteristics of ultra-thin-oxide nMOSFET's

Abstract: Ultra-thin gate oxide breakdown in nMOSFET's has been studied for an oxide thickness of 1.5 nm using constant voltage stressing. The pre-and post-oxide breakdown characteristics of the device have been compared, and the results have shown a strong dependence on the breakdown locations. The oxide breakdown near the source/drain-to-gate overlap regions was found to be more severe on the post-breakdown characteristics of the device than breakdown in the channel. This observation may be related to the dependence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…It was therefore suggested that SBD would not cause device or circuit failure in many applications [146]. However, Pompl et al [194] and others [135], [138], [195], [196] later showed that SBD will cause a significant increase in the transistor-off current if the breakdown spot is in the drain region, which is increasingly likely in short-channel devices. This will be referred to as "device breakdown."…”
Section: B Device Breakdownmentioning
confidence: 99%
“…It was therefore suggested that SBD would not cause device or circuit failure in many applications [146]. However, Pompl et al [194] and others [135], [138], [195], [196] later showed that SBD will cause a significant increase in the transistor-off current if the breakdown spot is in the drain region, which is increasingly likely in short-channel devices. This will be referred to as "device breakdown."…”
Section: B Device Breakdownmentioning
confidence: 99%
“…C-V curves were measured from inversion to accumulation region, under illumination in the beginning of the C-V extraction, at different frequencies of 1M, 1k, 100 and 20 Hz, as shown in Fig [. Accumulation capacitance decrease has 1 ,()x1 ()., been observed in high-frequency C-V curves from hafnium aluminate gate dielectrics, due to gate leakage current and series resistance as reported in references [11,14], in addition to errors associated with the measurement instrument as stated by references [10,15]. In Fig.…”
Section: Resultsmentioning
confidence: 82%
“…As a result, the physical thickness was (15.5±0.2) nm and it should represent a thick thickness far away from presenting tunneling and leakage current [15].…”
Section: Resultsmentioning
confidence: 99%
“…ITRS requirements (specified for the off-state region) are still met by the overall leakage current; however, when the device is turned on, much larger DT gate currents arise. Just for comparison, smaller currents, for instance induced by Soft Breakdown, usually motivate some concern [15]. This increases power dissipation and could, in principle, endanger circuit functionality.…”
Section: Discussionmentioning
confidence: 99%